PENGARUH MODAL INTELEKTUAL TERHADAP POTENSI PERTUMBUHAN PERUSAHAAN (Studi pada Perusahaan Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia) - Wardany, Yunida Hary (Jurnal Ilmiah Mahasiswa FEB, 2017)
The  objective  of  this  research  is  to  investigate  the  influence  of intellectual capital on the growth potential of companies. The intellectual capital is measured using VAIC™ method, which has three components, i.e. capital employed,  measured  using  Value  Added Capital  Employed  (VACA),  human capital, measured using Value Added Human Capital (VAHU), and structural capital,  measured using Structural  Capital  Value Added  (STVA).  The  growth potential of companies is measured using   Market to Book Value of Equity ratio (MVE/BVE). The population of this research is conventional banking companies with the total of 109 companies. Using purposive sampling methods, 95 conventional banking companies during 2013-2015 with specific criteria were selected. The data were analyzed through multiple linear regression analysis, and the hypotheses were tested using t test. The results of this research show that intellectual capital (VAIC) components that positively influence the growth potential of companies (Market to Book Value of Equity) is structural capital (STVA). It shows that Indonesian conventional banking companies use their structural capital, which is measured using STVA, to create added value that ultimately improve the company’s growth.Keywords: intellectual capital, the growth potential of company